Clarifying the mechanism of idiopathic macular hole development in fellow eyes using spectral-domain optical coherence tomography - Mikiko Takezawa (Dove Medical Press, 2011)
Mikiko Takezawa, Fumihiko Toyoda, Chiho Kambara, Hiroko Yamagami, Akihiro KakehashiDepartment of Ophthalmology, Jichi Medical University, Saitama Medical Center, Saitama, JapanBackground: To clarify the mechanism of idiopathic macular hole development, we evaluated the vitreoretinal relationship in fellow eyes of those with a macular hole and normal eyes using spectral-domain optical coherence tomography. Thirty-one fellow eyes and 34 normal volunteer eyes without a posterior vitreous detachment (PVD) were included.Results: We classified six vitreomacular relationships: type 1, no PVD, five fellow eyes (16.1%) and nine control eyes (26.5%); type 2, shallow PVD with perifoveal vitreous attachment, seven fellow eyes (22.6%) and 19 control eyes (55.9%); type 3, shallow PVD with pinpoint foveal vitreous traction, seven fellow eyes (22.6%) and no control eyes (0%), type 4a; shallow PVD with a round defect in the posterior vitreous cortex over the perifoveal area with vitreous attachment to the perifoveal area, two fellow eyes (6.5%) and one control eye (2.9%); type 4b, shallow PVD with a round defect in the posterior vitreous cortex over the perifoveal area without vitreous attachment to the perifoveal area, no fellow eyes (0%) and one control eye (2.9%); type 5a, shallow PVD with no pseudo-operculum, no fellow eyes (0%) and four control eyes (11.8%); type 5b, shallow PVD with a pseudo-operculum, four fellow eyes (12.9%) and no control eyes (0%); and type 6, biomicroscopically relevant PVD, six fellow eyes (19.4%).Conclusion: Types 3 and 5b developed only in fellow eyes. Type 2 developed most often in normal eyes and seemed to cause less foveal stress. Type 3 may show the basic pathogenesis of macular holes. Progression of type 5b after type 3 induces abortion of developing macular holes.Keywords: idiopathic macular hole, optical coherence tomography, posterior vitreous detachment, fellow eye